Planning Standard Operational Procedure Waiters In Apply Chinese Style Table Set Up In Educational Hotel Polywangi Jinggo - Serungke, Mayang; Rachma Amalia, Firda; Nurhalimah, Nurhalimah (Jurnal Ekonomi, 2024)
The hotel industry plays an important role as a supporting sector in the tourism sector. The tourism sector is one aspect that can be utilized to develop the potential of each region. Standard Operating Procedures (SOP) are documents that contain the steps/systems of work in an organization. The aim of this research is to create a structured written recapitulation of the Chinese style table set up SOP document, find out the process of designing the Chinese style table set up SOP at the Poliwangi Jinggo Education hotel and find out the implementation of the Waiters SOP in implementing the Chinese style table set up at the Poliwangi Jinggo Education hotel . The research method used is a qualitative approach, the preparation of service SOP documents is carried out using the gap analysis method (GAP) where the preparation of SOP documents is carried out in accordance with ideal conditions according to (five) dimensions of service quality, namely: direct evidence ( standard operational procedure) , reliability ( reliability ) , responsiveness , assurance and empathy by comparing the existing conditions of the Chinese style table set up procedures at the Poliwangi Jinggo Education hotel. Then, to ensure the Chinese style table set up SOP document produced is in accordance with the company's needs , then the verification and validation stages are carried out regarding the SOP documents created. The results of this research are standard operational procedures for Waiters in implementing Chinese style table set up at the Poliwangi Jingo Education Hotel. This SOP (standard operational procedure) is expected to become a document for the Poliwangi Jinggo Education Hotel and can also be a reference and guide for handling Chinese style table set ups in food and beverage